The Influence of Sanitation and Hygiene Systems on The Existence of Escherichia Coli Bacteria in Products of Pindang Fish at Kusamba Centers, Klungkung, Bali - Ni Wayan Sulastri; Ni Putu Pandawani; Ketut Widnyana; I Made Wahyu Wijaya (Advances in Tropical Biodiversity and Environmental Sciences, 2023)
Hygiene and sanitation are essential factors in fish processing to ensure food availability and safety. Escherichia coli causes foodborne illness, originating from pindang fish from the Kusamba breeding center, Klungkung Regency, Bali. Availability and security of food cover cleanliness are essential to hygiene and sanitation, where Escherichia coli indicates food contamination. This study aims to determine the bacteriological quality of boiled pindang products and the effect of sanitation and hygiene on the presence of E. coli in pindang products conducted at the Fish Preservation Center in Kusamba Village, Klungkung, Bali in November-December 2022. The study used a quantitative method with a cross-sectional approach and analysis. The laboratory uses the MPN (Most Probable Number). I was preparing a handling strategy with a SWOT analysis. The results showed that environmental sanitation and personal hygiene had a significant effect. MPN test results obtained a positive percentage of 93.1% and a negative of 6.9%. Of the 44 hospital wards, the results could have been better in environmental sanitation at 11.3 %, equipment sanitation at 6.8%, and personal hygiene at 8.1%. The implementation strategy to minimize the presence of E.coli bacteria is maintaining the unity of the quality system by carrying out sanitation and hygiene, starting from raw materials, processes, and products.